Role of Statin Drugs for Polycystic Ovary Syndrome - Lisa Cassidy Vu; Edwina Joe; Julienne K Kirk (Tehran University of Medical Sciences, 2017)
Objective: To review the potential role and specific impact of statin drugs in women with PCOS. The evidence for this use of statins in PCOS is limited and still under further investigation. Materials and methods: A search was conducted using PubMed, DynaMed and PubMedHealth databases through October 16, 2016 using the terms polycystic ovary syndrome, PCOS, hydroxymethylglutaryl-CoA reductase inhibitors, hydroxymethylglutaryl-CoA , statin, atorvastatin, fluvastatin, lovastatin, pitavastatin, pravastatin, rosuvastatin and simvastatin. English-language trials evaluating statins in PCOS were obtained and incorporated if they provided relevant data for providers. Results: We summarize twelve trials involving statins in PCOS. The trials were predominantly 12 weeks to 3 months in length (8 of the 12 trials) and low to moderate dose of statin drugs were used. The majority (10 of 12) of the trials show that statins reduce testosterone levels or other androgen hormones (DHEA-S and androstenedione), half of the trials evaluating LH/FSH ratio show an improvement, and all had positive effects on lipid profiles. Conclusion: Statins show promising improvements in serum levels of androgens and LH/FSH ratios translating to improved cardiovascular risk factors above and beyond simply lowering LDL levels. More investigation is needed to determine if statins can clinically impact women with PCOS long term, particularly those who are young and are not yet candidates for traditional preventative treatment with a statin medication.